Contemporary outcomes of metastatic breast cancer among 22, 000 women from the multicentre ESME cohort 2008–2016. (April 2020) - Deluche, Elise; Antoine, Alison; Bachelot, Thomas; Lardy-Cleaud, Audrey; Dieras, Veronique; Brain, Etienne; Debled, Marc; Jacot, William; Mouret-Reynier, Marie Ange; Goncalves, Anthony; Dalenc, Florence; Patsouris, Anne; et al.
Abstract: Aim: Real-world data inform the outcome comparisons and help the development of new therapeutic strategies. To this end, we aimed to describe the full characteristics and outcomes in the Epidemiological Strategy and Medical Economics (ESME) cohort, a large national contemporary observational database of patients with metastatic breast cancer (MBC). Methods: Women aged ≥18 years with newly diagnosed MBC and who initiated MBC treatment between January 2008 and December 2016 in one of the 18 French Comprehensive Cancer Centers (N = 22, 109) were included. We assessed the full patients' characteristics, first-line treatments, overall survival (OS) and first-line progression-free survival, as well as updated prognostic factors in the whole cohort and among the 3 major subtypes: hormone receptor positive and HER2-negative (HR+/HER2−, n = 13, 656), HER2-positive (HER2+, n = 4017) and triple-negative (n = 2963) tumours. Results: The median OS of the whole cohort was 39.5 months (95% confidence interval [CI], 38.7–40.3). Five-year OS was 33.8%. OS differed significantly between the 3 subtypes (p < 0.0001) with a median OS of 43.3 (95% CI, 42.5–44.5) in HR+/HER2−; 50.1 (95% CI, 47.6–53.1) in HER2+; and 14.8 months (95% CI, 14.1–15.5) in triple-negative subgroups, respectively. Beyond performance status, the following variables had a constant significant negative prognostic impact on OS in the whole cohort and among subtypes: older age at diagnosis of metastases (except for the triple-negative subtype), metastasis-free interval between 6 and 24 months, presence of visceral metastases and number of metastatic sites ≥ 3. Conclusions: The ESME program represents a unique large-scale real-life cohort on MBC. This study highlights important situations of high medical need within MBC patients. Database registration: clinicaltrials.gov Identifier NCT032753. Highlights: ESME provides a full picture of the real-life overall survival (OS) of women diagnosed with metastatic breast cancer from 2008 till 2016. The median OS of the whole population over this 9-year period was 39.5 months (95% confidence interval, 38.7–40.3). Prognostic factors on OS were age, tumour subtype, metastasis-free interval, presence of visceral metastases and number of metastatic sites.